Pendidikan Karakter Profetik dalam Sirah Nabawiyah (Telaah Kitab al-Râhiq al-Makhtûm Karya Shafiy al-Rahmân al-Mubârakfuri) - Syahid, Ahmad; Husni, H. (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2018)
This study aims to analyze the character values ​​in Sirah Nabawiyah Ar-Rahiq Al-Makhtum by Syafiyyurrahman al-Mubarakfuri, so that it is revealed how the character education of the Prophet Muhammad. and analyze its relevance to current educational goals. The research method used is library research, the type of research approach is deductive and the analysis method is content analysis. Data collection techniques used were library techniques. This research succeeded in proving that prophetic values ​​based on the history of the Prophet Muhammad have a strong relevance to the concept of contemporary character education. Prophetic values ​​loaded with character education in this era, especially related to religiosity, honesty, tolerance, discipline, hard work, creative, independent, democracy, curiosity, national spirit, love of the motherland, respect for achievement, friendship, love for peace , likes to read, care about the environment, care about social, and responsibility.